2018
DOI: 10.1111/jnc.14451
|View full text |Cite
|
Sign up to set email alerts
|

Hearing vulnerability after noise exposure in a mouse model of reactive oxygen species overproduction

Abstract: Previous studies have convincingly argued that reactive oxygen species (ROS) contribute to the development of several major types of sensorineural hearing loss, such as noise-induced hearing loss (NIHL), drug-induced hearing loss, and age-related hearing loss. However, the underlying molecular mechanisms induced by ROS in these pathologies remain unclear. To resolve this issue, we established an in vivo model of ROS overproduction by generating a transgenic (TG) mouse line expressing the human NADPH oxidase 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 63 publications
(160 reference statements)
0
14
0
Order By: Relevance
“…Twomonth-old control, Nox3-Cre +/− ;tdTomato +/+ , and Nox3-Cre +/+ ;tdTomato +/+ (Nox3-KO) mice were anesthetized as described and exposed to octave-band noise at 120 dB SPL centered at 8 kHz for 3 h inside a sound chamber. The condition of NE to induce a permanent threshold shift was determined based on our previous report (Morioka et al, 2018). Each animal was placed in a cage in the sound chamber, which was fitted with a speaker (300 HT; FOSTEX, Akishima, Japan) driven by a noise generator (SF-06; RION, Kokubunji, Japan) and power amplifier (DAD-M100proHT;…”
Section: Age-related Cisplatin-induced and Noise-induced Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Twomonth-old control, Nox3-Cre +/− ;tdTomato +/+ , and Nox3-Cre +/+ ;tdTomato +/+ (Nox3-KO) mice were anesthetized as described and exposed to octave-band noise at 120 dB SPL centered at 8 kHz for 3 h inside a sound chamber. The condition of NE to induce a permanent threshold shift was determined based on our previous report (Morioka et al, 2018). Each animal was placed in a cage in the sound chamber, which was fitted with a speaker (300 HT; FOSTEX, Akishima, Japan) driven by a noise generator (SF-06; RION, Kokubunji, Japan) and power amplifier (DAD-M100proHT;…”
Section: Age-related Cisplatin-induced and Noise-induced Hearing Lossmentioning
confidence: 99%
“…There are seven isoforms in humans (NOX1-5, DUOX1-2), and previous studies have demonstrated that ROS contribute to ARHL, DIHL, and NIHL ( Kamogashira et al, 2015 ). Recently, we reported a transgenic mouse line that expresses NOX4 , which produces low levels of ROS without stimulation, exhibits hearing vulnerability after noise exposure (NE) ( Morioka et al, 2018 ), further indicating that ROS contribute to SNHL.…”
Section: Introductionmentioning
confidence: 99%
“…Four-week-old DIA1 TG/TG mice and littermate control WT mice were anesthetized with the anesthetic cocktail and exposed to octave-band-noise, centered at 8 kHz, for 1 h at 105 dB SPL in a sound chamber, as described previously 57 . Each animal was placed in the center of the chamber.…”
Section: Noise Exposurementioning
confidence: 99%
“…ROS-induced oxidative stress has been reported to play a key role in several systems and in cochlear damage [132][133][134][135][136]. Numerous studies have demonstrated that the accumulation of ROS and subsequent apoptosis induction promote several major types of SNHL, including noise-induced hearing loss, drug-induced hearing loss, and age-related hearing loss [137][138][139][140][141][142]. ROS are considered to be toxic products of cell metabolism and are signaling molecules that regulate a variety of physiological processes.…”
Section: Oxidative Stress and Ros Signalingmentioning
confidence: 99%